2013
DOI: 10.1097/aog.0000000000000012
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Pelvic Floor Muscle Training and Urinary Incontinence

Abstract: : I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
1
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 26 publications
1
84
1
13
Order By: Relevance
“…This concurs with previous findings that efficacy of PFME is associated with high adherence to the treatment protocol. 4,21 Thus, our results may indicate that PFME frequency and intensity has a major role in reducing postpartum AI symptoms. One in five women failed to attend their post-intervention appointment and this may have resulted in the discrepancies between the un-imputed and the intention-to-treat analyses.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This concurs with previous findings that efficacy of PFME is associated with high adherence to the treatment protocol. 4,21 Thus, our results may indicate that PFME frequency and intensity has a major role in reducing postpartum AI symptoms. One in five women failed to attend their post-intervention appointment and this may have resulted in the discrepancies between the un-imputed and the intention-to-treat analyses.…”
Section: Discussionmentioning
confidence: 85%
“…21 Further, a recent Cochrane review concluded that targeted PFME intervention in populations with AI was more effective than mixed prevention and treatment approaches. 4 The success of PFME depends on the patients' ability to actively contract the pelvic floor muscles, and Bø et al 22 demonstrated that 30% of the participating women were unable to perform a correct VPFMC on the first attempt.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion rate was 29% (n = 87): five women were excluded for premature delivery or stillbirth; 11 women were excluded postpartum for new pregnancies; and 71 women were excluded from the two last visits because they participated in the intervention group of an RCT exploring the effect of postpartum pelvic floor muscle training. 23,24 Data for the latter two groups were collected, but were considered ineligible for analysis because of the potential effects of pregnancy or training on the POP-Q score. The drop-out rate in this study was 11% (n = 34).…”
Section: Resultsmentioning
confidence: 99%
“…Continuing exclusion criteria were premature delivery prior to 32 weeks of gestation, stillbirth, having a new pregnancy of more than 6 weeks of gestation in the postpartum period, and participation in the intervention group of a randomised controlled trial (RCT) evaluating the effect of postpartum pelvic floor muscle training. 23,24 The RCT recruitment took place at 6 weeks postpartum, including participants with vaginal deliveries. No a priori power calculation was performed for the outcomes of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Excluded records 36 records were excluded; seven (Spreafico, 1992;Cox, 1995; Pelvic floor muscle training for prevention and treatment of urinary and faecal incontinence in antenatal and postnatal women, Bø, 2011;Duffin, 2012;Rathfisch and Kızılkaya Bejı, 2012;Freeman, 2013) because they were not primary studies, and 24 (Sleep and Grant, 1987;Dougherty et al, 1989;Sampselle et al, 1998;Glazener et al, 2001;Meyer et al, 2001;Sanlorenzo et al, 2001;Cockburn, 2002, Chiarelli et al, 2004;Dumoulin, 2004;Dumoulin et al, 2004;Gorbea Chavez et al, 2004, Erratum, 2005Ewings et al, 2005;Glazener et al, 2005;Lee and Choi, 2006;Citak et al, 2010;Sheeba et al, 2011;Kim et al, 2012;Ahlund et al, 2013, Assis et al, 2013Dumoulin et al, 2013;Hilde et al, 2013;Peirce et al, 2013;Glazener et al, 2014) because they did not research the use of cones or balls but the usual pelvic floor exercises without device. and (same study) was not a randomised controlled trial; in Jonasson et al (1992), women were at least two years post partum.…”
Section: Included Studymentioning
confidence: 99%